Digital Public Relations: Trend and Required Skills - Alfelia Nugky Permatasari; Endang Soelistiyowati; I Gusti Ayu Putu Puji Suastami; Riski Apriliani Johan (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Public Relations have evolved adjusting its practices to fulfill the needs of its users. In this case, technology possesses a great influence on how PR operates and interacts within society. Various institutions move to digital Public Relations, relying heavily on digital platforms, forcing Public Relations practitioners to master a new set of skills. This research aimed to map digital public relations trends and investigate the digital public relations competencies needed. A number of public relations practitioners from various institutions were interviewed to meet the objectives. A qualitative descriptive approach was used to answer the research questions. The research found that today traditional and digital public relations work synergically and are still needed by organizations. Apart from having good communication, interpersonal, writing, analytical thinking, and soft skills, a public relations practitioner is expected to be familiar with the digital platform and have the ability to design digital content.